2017
DOI: 10.5455/apd.276919
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caregivers' social anxiety, aggression and attachment style on the severity of schizophrenia

Abstract: _____________________________________________________________________________________________________ ÖZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Literature showed that most women take responsibility for providing care. 1,17,22,23 The studies performed with caregivers of schizophrenia patients showed that 61.9% of caregivers in Taiwan, 80.0% of caregivers in China, 73.7% of caregivers in Iran and 74.0% of caregivers in India are women and married. 6,[24][25][26] We may suggest that the because of her position in the home and being more prone to giving care, most women take responsibility for the care of the schizophrenic patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature showed that most women take responsibility for providing care. 1,17,22,23 The studies performed with caregivers of schizophrenia patients showed that 61.9% of caregivers in Taiwan, 80.0% of caregivers in China, 73.7% of caregivers in Iran and 74.0% of caregivers in India are women and married. 6,[24][25][26] We may suggest that the because of her position in the home and being more prone to giving care, most women take responsibility for the care of the schizophrenic patient.…”
Section: Resultsmentioning
confidence: 99%
“…11,15,16 Caregivers of chronic psychiatric patients experience emotions such as stress, anxiety, low self-perception, shame, guilt, fear, despair, strain, anxiety, anger, hopelessness, social isolation, loss, and depression. 14,15,17,18 It has been stated that anxiety levels in caregivers of schizophrenia patients are generally high. 5 Identifying the difficulties in care period, providing professional assistance and consultancy will empower the caregiver against the negative effects of care burden, and will contribute to the maintenance of well-being both in the caregiver and the patient.…”
mentioning
confidence: 99%